(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to examine the impact of the work environment on the quality of hotel services from the perspective of employees at Bab Al-Bahr Hotel in Tripoli. The descriptive-analytical approach was adopted, and a questionnaire was used as the main data collection tool. A simple random sample of 50 employees participated in the study. Data were analyzed using SPSS through descriptive statistical techniques including frequencies, percentages, means, and standard deviations. The findings indicated that the work environment achieved a high level with an overall mean of 4.06, while the quality of hotel services also recorded a high level with an overall mean of approximately 4.14. The highest-rated aspects included workplace cleanliness, organization, occupational safety, and employees’ professional appearance. In contrast, incentives, employee recognition, and continuous efforts to enhance guest satisfaction received comparatively lower ratings despite remaining at a high level. The study recommends improving incentive systems, expanding employee training programs, involving employees in decision-making, and continuously enhancing hotel service quality.